The involvement of T lymphocytes in the pathogenesis of endometriotic tissues overgrowth in women with endometriosis. - Szyllo, Krzysztof (2003)
BACKGROUND: Endometriosis, uncontrolled proliferation of ectopic and eutopic endometriotic tissues, is common in women at reproductive age, and may affect fertility. The role of macrophages in the pathogenesis is well proved, but engagement of T cells in the pathogenesis of endometriosis is a matter of controversy. AIMS: T-cell involvement in the pathogenesis of endometriosis was the objective of our study performed on women aged 24-46 years with diagnosed endometriosis. All the patients that were studied underwent diagnostic laparoscopy. METHODS: We evaluated the distribution of T-lymphocyte subpopulations in peripheral blood (PB), peritoneal fluid (PF) and in endometriotic tissues (ET), as well as cytokines [interleukin (IL)-2, IL-4, IL-10, IL-12, interferon (IFN)-gamma] production by peripheral blood lymphocytes. IFN-gamma, tumor necrosis factor (TNF)-alpha, IL-4 and IL-6 were investigated for their intracellular presence. The experiments were carried out before and after 6 months treatment with the GnRH-Analogous Goserelin (Zeneca Pharmaceuticals). The number of performed investigations is presented. Statistical analysis was performed using Statistica/Win 5.0 software and Student's t-test, the paired Student t-test and Fisher's exact test when appropriate. RESULTS: We have compared the lymphocyte subset re-distribution with regard to the American Fertility Society (AFS) stages and scores, but no differences were observed. The significant increase in CD4:CD8 ratio, the decrease in the number of natural killer (NK) cells in PB and the decrease in CD4:CD8 ratio in PF and ET of women with endometriosis was noted. The diminished IFN-gamma secretion by phytohemagglutinim (PHA)-stimulated lymphocytes in vitro derived from women with endometriosis and increased IL-4 production may be responsible for defective immunosurveillance against overgrowth of endometriotic tissues. The diminished NK cells number in PB of women with endometriosis argues for such a hypothesis. The increased deposits of proinflammatory IL-6 and TNF-alpha in the T lymphocytes of women with endometriosis may be related to T-regulatory lymphocyte function and their inability to suppress cell proliferation in endometriosis. GnRH-Analogous Goserelin treatment normalises cytokine production and induces patient recovery. CONCLUSIONS: The significant functional and phenotypic differences between the lymphocytes from healthy women and women with endometriosis were noted. The diminished IFN-gamma production in relation to decreased NK cells number and the increased IL-4 production before the treatment and normalisation after the treatment suggest the involvement of the deregulated T-cell system in the growth stimulation and recruitment of endometriotic cells. The increased CD4:CD8 ratio, IL-6, TNF-alpha deposits and diminished anti-inflammatory IL-10 production by lymphocytes may participate in the pathogenesis of endometriosis, and may secondarily affect the monocyte/macrophage function.